Policy Ambiguity and Regulative Legitimacy of Technology : Legal Indeterminacy as Result of an Ambiguous Taximeter Regulation - Väyrynen, Karin; Lanamäki, Arto (Association for Information Systems (AIS), 2020)
Institutions influence the design, use and adoption of information technologies. The IS field has a long tradition in institutional analyses, especially concerning how ICT gains legitimacy in organizational settings. However, few analyses have been con-ducted on how legal reforms influence regulative ICT legitimacy. We studied the ef-fect of policy ambiguity on regulative legitimacy through a revelatory case study of a legal reform concerning the taximeter regulation in Finland. The regulation changed from being specific and providing legal certainty to being ambiguous and resulting in legal indeterminacy. We contribute to the IS institutions and legitimacy research stream by arguing that the transition from specific to ambiguous regulation shifted the locus of regulative legitimacy from an inherent property of legal formulation to a processual form, and provide a framework to support studies on regulative change by distinguishing between type of policy and legal state of the technology. Our study has methodological implications.
Keywords: Regulative legitimacy; policy ambiguity; legal reforms; technology-in-use; regulation; fi=Viestintätieteet|en=Communication Studies|